2014
DOI: 10.1180/minmag.2014.078.7.13
|View full text |Cite
|
Sign up to set email alerts
|

Unique thallium mineralization in the fumaroles of the Tolbachik volcano, Kamchatka Peninsula, Russia. II. Karpovite, Tl2VO(SO4)2(H2O)

Abstract: Karpovite, ideally Tl2VO(SO4)2(H2O), was found in a fumarole of the 1st cinder cone of the North Breach of the Great Fissure Tolbachik volcano eruption (1975–1976), Kamchatka Peninsula, Russia. Karpovite occurs as bundles of white, needle-like crystals associated with shcherbinaite, pauflerite, bobjonesite, markhininite, evdokimovite and microcrystalline Mg, Al, Fe and Na sulfates. Karpovite is monoclinic, P21, a = 4.6524(4), b = 11.0757(9), c = 9.3876(7) Å , β = 98.353(2)º, V = 478.60(7) Å3, Z = 2 (from singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, it should be noted that transformation and decomposition of kröhnkite revealed in the course of our HTXRD study is different as reported below. Kröhnkite-type compounds with various octahedrally coordinated cations and T 6+ O 4 ( T 6+ = S, Cr and Se) groups are abundant in both minerals and synthetic compounds (Driscoll et al ., 2016; Marinova et al ., 2015; Siidra et al ., 2014; Barpanda et al ., 2014; Saha et al ., 2011; Yang et al ., 2011; Stoilova et al ., 2009 a , b ; Wierzbicka-Wieczorek et al ., 2008; Behera and Rao, 2006; Kolitsch and Fleck, 2005, 2006; Fleck and Kolitsch, 2003; Wildner and Stoilova, 2003; Pasha et al ., 2003; Fleck et al ., 2002 a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that transformation and decomposition of kröhnkite revealed in the course of our HTXRD study is different as reported below. Kröhnkite-type compounds with various octahedrally coordinated cations and T 6+ O 4 ( T 6+ = S, Cr and Se) groups are abundant in both minerals and synthetic compounds (Driscoll et al ., 2016; Marinova et al ., 2015; Siidra et al ., 2014; Barpanda et al ., 2014; Saha et al ., 2011; Yang et al ., 2011; Stoilova et al ., 2009 a , b ; Wierzbicka-Wieczorek et al ., 2008; Behera and Rao, 2006; Kolitsch and Fleck, 2005, 2006; Fleck and Kolitsch, 2003; Wildner and Stoilova, 2003; Pasha et al ., 2003; Fleck et al ., 2002 a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…In each octahedron, there is one short VO vanadyl bond (1.60, 1.61 and 1.56 Å for V1, V2, and V3, respectively) opposite to one long VÀH 2 O bond (2.31, 2.19 and 2.21 Å for V1, V2 and V3, respectively). The coordination of V 4+ in evdokimovite is similar to that in the structure of karpovite (Siidra et al, 2014b) and is typical for vanadium oxysalts with V 4+ in [1+4+1] coordination (Schindler et al, 2000).…”
Section: Crystal Structure Experimentalmentioning
confidence: 56%
“…The crystal structure of evdokimovite is unique among known oxysalt minerals and synthetic compounds (Krivovichev, 2009) Figure 7 provides graph representations and indicates close structural relationships of the heteropolyhedral units observed in markhininite (Siidra et al, 2014a), karpovite (Siidra et al, 2014b) and evdokimovite. The structure of evdokimovite is strongly controlled by the stereochemical activity of the so-called 'lone electron pairs' on the Tl + cations.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations